2013
DOI: 10.4028/www.scientific.net/amm.300-301.1289
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanical Properties of ABS Enhanced by Magnesium Hydroxide Whiskers

Abstract: magnesium hydroxide whiskers; ABS; mechanical properties Abstract: The magnesium hydroxide (MH) whiskers/ABS composites were prepared by melt-extrusion with whiskers as fillers. Zinc stearate was used as modifier to improve the compatibility of the composites. The mechanical properties of ABS enhanced by different cotents of magnesium hydroxide whiskers were tested by the RGT-10 universal testing machine. When the content of whiskers was 10%, The comprehensive mechanical properties of the composites were the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, the presence of more than 10 % MH reduces the tensile strength non-linearly. [25] As can be seen in Table 3, the presence of ZB in the ABS-based composites led to higher decrease in tensile strength values. The use of an excessive amount of FR additives may have caused accumulation in the polymer structure, which may have led to a decrease in tensile strength.…”
Section: Mechanical Propertiesmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the presence of more than 10 % MH reduces the tensile strength non-linearly. [25] As can be seen in Table 3, the presence of ZB in the ABS-based composites led to higher decrease in tensile strength values. The use of an excessive amount of FR additives may have caused accumulation in the polymer structure, which may have led to a decrease in tensile strength.…”
Section: Mechanical Propertiesmentioning
confidence: 84%
“…The use of a higher ratio of FR appears to result in lower PHRR values, indicating slower flame spread and better fire resistance. [25] In addition, MH and ZB additions decreased the pHRR value. When the 3 % wt % MH and ZB additives were compared according to the data in Table 8, it was observed that MH caused a lower pHHR value.…”
Section: Cone Calorimeter Analysismentioning
confidence: 97%
“…Moreover, the performance of the matrix as flame retardant is also improved and the application range of the composites is expanded. Since magnesium salt whiskers / polymer matrix composites not only has excellent mechanical properties, but also has good flame retardant properties, it has a broad application in building materials, chemical industry, motorcycle parts manufacturing, daily necessities, household appliances and transportation interiors etc [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%